2017
DOI: 10.2147/opth.s150022
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Keraring implantation and corneal cross-linking for the treatment of keratoconus in children with vernal keratoconjunctivitis

Abstract: PurposeThe purpose of this study was to assess the safety and efficacy of femtosecond laser-assisted Keraring implantation followed by transepithelial accelerated corneal collagen cross-linking (CXL) for the treatment of keratoconus in children with vernal keratoconjunctivitis (VKC).Study designThis is a prospective interventional non-comparative case series.Patients and methodsEighteen eyes of 11 children with keratoconus and VKC were included in this study. All the cases were treated with femtosecond laser-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…36% of patients complained of a transient burning sensation during treatment Medium–low Chatterjee and Agrawal [ 114 ] 2016 India 23 14.7 To evaluate the efficacy of 0.03% tacrolimus ointment in the treatment of VKC Symptom and signs significantly reduced at 4 and 12 weeks ( p < 0.0001). Visual acuity showed an improvement after 12 weeks of treatment ( p = 0.05) High Yücel and Ulus [ 115 ] 2016 Turkey 30 12.9 To evaluate the efficacy and safety of topical cyclosporine A 0.05% in the treatment of VKC Topical CsA 0.05% (Restasis®) was effective in reducing VKC signs and symptoms ( p < 0.001) Medium–low Abozaid [ 116 ] 2017 Egypt 11 13.6 To assess the safety and efficacy of femtosecond laser-assisted Keraring implantation followed by transepithelial accelerated corneal collagen cross-linking (CXL) for the treatment of keratoconus in children with VKC All the eyes treated showed an improvement in visual acuity, keratometry values and refraction ( p < 0.001). No intraoperative complications were reported Medium Al-Amri et al [ 117 ] 2017 Saudi Arabia 20 16.9 To evaluate the safety and efficacy of 0.003% tacrolimus suspension for the treatment of refractory VKC 6 weeks of tacrolimus 0.003% therapy permitted a significant improvement in VKC symptoms ( p < 0.001) and signs ( p < 0.001), with no important side effects Medium–low Costa et al [ 118 ] 2017 Brazil 17 12.3 To evaluate the use of supratarsal injection of triamcinolone acetonide in severe VKC …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…36% of patients complained of a transient burning sensation during treatment Medium–low Chatterjee and Agrawal [ 114 ] 2016 India 23 14.7 To evaluate the efficacy of 0.03% tacrolimus ointment in the treatment of VKC Symptom and signs significantly reduced at 4 and 12 weeks ( p < 0.0001). Visual acuity showed an improvement after 12 weeks of treatment ( p = 0.05) High Yücel and Ulus [ 115 ] 2016 Turkey 30 12.9 To evaluate the efficacy and safety of topical cyclosporine A 0.05% in the treatment of VKC Topical CsA 0.05% (Restasis®) was effective in reducing VKC signs and symptoms ( p < 0.001) Medium–low Abozaid [ 116 ] 2017 Egypt 11 13.6 To assess the safety and efficacy of femtosecond laser-assisted Keraring implantation followed by transepithelial accelerated corneal collagen cross-linking (CXL) for the treatment of keratoconus in children with VKC All the eyes treated showed an improvement in visual acuity, keratometry values and refraction ( p < 0.001). No intraoperative complications were reported Medium Al-Amri et al [ 117 ] 2017 Saudi Arabia 20 16.9 To evaluate the safety and efficacy of 0.003% tacrolimus suspension for the treatment of refractory VKC 6 weeks of tacrolimus 0.003% therapy permitted a significant improvement in VKC symptoms ( p < 0.001) and signs ( p < 0.001), with no important side effects Medium–low Costa et al [ 118 ] 2017 Brazil 17 12.3 To evaluate the use of supratarsal injection of triamcinolone acetonide in severe VKC …”
Section: Resultsmentioning
confidence: 99%
“…In 2017, Abozaid [ 116 ] tried to assess the safety and efficacy of femtosecond laser-assisted Keraring implantation followed by transepithelial accelerated corneal collagen cross-linking (CXL) for the treatment of keratoconus in children with VKC. In their observational study, all the eyes treated showed an improvement in visual acuity, keratometry values, and refraction ( p < 0.001).…”
Section: Therapymentioning
confidence: 99%
“…In his prospective pilot study on children with keratoconus and VKC,13 Abozaid proved the safety and efficacy after one year of femtosecond laser-assisted keraring implantation followed by transepithelial cross linking. Unlike his study, this study was retrospective, had longer follow-up duration, had larger sample size, had a control group with CXL alone, and studied more parameters such as the corneal volume, Q value, and vector analysis of the astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Keratoconus is a relatively common eye condition in upper Egypt where the climate is hot and dry. 1,2 It is a type of corneal ectasia characterized by thinning of the corneal stroma which assumes a conical shape resulting in progressive deterioration of vision secondary to induced myopia, astigmatism, and high order aberrations.…”
Section: Introductionmentioning
confidence: 99%